Comparative study of frequency domain filtered-x LMS algorithms applied to vehicle powertrain noise control. (11th November 2009) - Duan, Jie; Li, Mingfeng; Lim, Teik C.; Lee, Ming-Ran; Vanhaaften, F.; Cheng, Ming-Te; Abe, Takeshi
Currently, passive noise control treatment is widely applied to treat vehicle powertrain noise. However, passive noise control technology is often not effective in the low frequency range where the response is typically the most dominant component. With the rapid development of digital signal processing, active noise control (ANC) can be a feasible alternative. In this study, an enhanced frequency domain filtered-x least mean square (FXLMS) algorithm is proposed as the basis of an active control system for treating powertrain interior noise. Compared to the time domain algorithms, the approach can save computing time especially for long controller's filter length. Furthermore, unlike traditional ANC techniques for suppressing response, the proposed frequency domain FXLMS algorithm is targeted at tuning vehicle interior response in order to achieve a desirable sound quality. Several frequency domain algorithms are studied numerically by applying the analysis to treat vehicle interior noise recorded from an actual vehicle.